Moist Air Flow Analysis in an Open Enclosure. Part A: Parametric Study - Chati, T.; Rahmani, K.; Naas, T. T.; Rouibah, A. (Engineering, Technology & Applied Science Research, 2021)
Heat and mass transfer in many systems are widely accomplished applying natural convection process due to their low cost, reliability, and easy support. Typical applications include different mechanisms in various fields such as (solar energy, solar distiller, stream cooling, etc…). Numerical results of turbulent natural convection and mass transfer in an open enclosure for different aspect ratios (AR = 0.5, 1, and 2) with a humid-air are carried out. Mass fraction and local Nusselt number were proposed to investigate the heat and mass transfer. A heat flux boundary conditions were subjected to the lateral walls and the bottom one make as an adiabatic wall, while the top area was proposed as a free surface. Effect of Rayleigh numbers (106≤????????≤108) on natural convection and mass flow behavior are analyzed. The governing equations are solved using CFD Fluent code based on the SIMPLE algorithm. The results showed that the cavity with an aspect ratio of AR = 2 has a significant enhancement to raise the rates of both heat and mass transfer. When the Rayleigh number increases, maximum heat transfer rates were observed due to the fluid flow becomes more vigorous. However, mass transfer improves as the Rayleigh number decreases.